How transfer of knowledge can be linked to productivity and competitiveness of the firm - theoretical considerations and case study - Westeren, Knut Ingar (Informe GEPEC, 2000)
The most important contribution management needs to make in the 21st century is to increase the productivity of knowledge work and knowledge workers. This is the point of departure for this article where we first give a theoretical discussion about how firms can utilize knowledge to improve competitiveness. This builds on the assumption that the firm’s utilization of tangible resources depends on how they are combined and applied, which is in turn, a function of the firm’s knowledge. In the empirical part of the article, we analyze how these processes take place in assembly line operations and support functions. The main result is that although knowledge itself is important, it is essential to develop an understanding of human resource developments on all levels of the managerial system of the firm and ensure that the managers are able to transfer knowledge between groups.